User Perceptions of a Home Automation System: A TAM-Based Evaluation - Yaldaie Ashkan; Porras Jari; Drögehorn Olaf (Applied Computer Systems, 2025)
The study explores user perceptions of a newly developed home automation system, using the Technology Acceptance Model (TAM) as a theoretical framework to guide the evaluation. The system includes advanced features for security, energy efficiency, and user convenience. It was tested in three different residential environments to evaluate its adaptability. Participants interacted with the system in a controlled laboratory setting and completed a structured survey. The study examines core TAM constructs – perceived ease of use, perceived usefulness, and behavioural intention – alongside additional factors such as trust and privacy concerns. The results highlight strong user satisfaction and intention to adopt the system, while also identifying areas for improvement, particularly in privacy assurance and device control. The findings offer practical recommendations for developers to enhance usability, transparency, and user trust. The research contributes to the smart home literature by demonstrating TAM’s applicability to real-world systems and by providing insights into the practical and user-centred factors that influence technology acceptance.